2010
DOI: 10.1097/brs.0b013e3181c6526b
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Occurrence of Heterotopic Ossification According to Prosthesis Type in the Cervical Artificial Disc Replacement

Abstract: Occurrence of HO is an inevitable postoperative complication after cervical ADR. The occurrence rate of HO was higher than our expectation. Moreover, definite differences in occurrence rate according to the prosthesis type were identified by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 13 publications
3
96
3
1
Order By: Relevance
“…Follow-up ranged from 24 to 96 months and the occurrence of HO ranged from 37.5 to 62 %. An early study of HO with the Bryan Cervical Disc [12] found that 17.8 % of the patients had developed HO 12 months after surgery. Yi et al [13] assessed HO after 20 months in both nonconstrained and semiconstrained devices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up ranged from 24 to 96 months and the occurrence of HO ranged from 37.5 to 62 %. An early study of HO with the Bryan Cervical Disc [12] found that 17.8 % of the patients had developed HO 12 months after surgery. Yi et al [13] assessed HO after 20 months in both nonconstrained and semiconstrained devices.…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of cervical arthroplasty, Mehren et al [10] published their classification system based on McAfee et al [9]. The degree of HO is described as low (grade 0-2) or high (grade 3-4) [10], and in the last decade several reports have been published in which the occurrence rate of HO varies according to the disc prosthesis used [11][12][13]. Cervical arthroplasty devices are usually manufactured to be semiconstrained or nonconstrained.…”
Section: Introductionmentioning
confidence: 99%
“…Qureshi et al analysed the cost-effectiveness comparing single level TDR and ACDF and conclude also that cTDR and ACDF are cost-effective procedures, but cTDR must remain functional for at least 14 years to establish greater cost-effectiveness than ACDF [34]. The appearance of HO right up to solid fusion (Grade 4) is a well known complication in cervical total disc replacement which can affect the motion, respectively, the function of the prosthesis [31,32,35] regardless the implant-type [7,11,17,27,28,[36][37][38][39]. The progression of HO into higher grades over time was also seen in other studies [28,32].…”
Section: Adjacent Segment Degenerationmentioning
confidence: 99%
“…In our study, 89.2 % of patients had an ossification Cgrade I at the 5-year follow-up. Many publications, however, reported that HO was not affecting clinical improvement [6,[19][20][21][22][23][24]. The clinical relevance of the low grade ossifications is questionable.…”
Section: Pain Relief Medication Consumption and Quality Of Lifementioning
confidence: 99%